Perbedaan Serum dan Plasma EDTA yang Langsung Diperiksa dan Ditunda 1 dan 2 Jam Terhadap Penurunan Kadar Glukosa Darah - Evriarti, Paulina Rosa; Lumban Toruan, Sari Artauli (Journal of Vocational Health Science, 2024)
Background: Serum and plasma are obtained after separating the liquid part of the blood cells through a centrifugation process. Before being separated, blood cells will use the glucose found in serum and plasma to maintain their viability. Purpose: Therefore, a study was conducted to determine the effect of delayed separation of serum and plasma on reducing glucose levels. Methods: Blood samples obtained from research subjects were divided into 2 groups (EDTA and without anticoagulants). Each group was divided into 3, for the 1st tube the serum and plasma were immediately separated, the 2nd tube was delayed 1 hour and the 3rd tube was delayed 2 hours. All samples were measured for glucose levels using the GOD-PAP method. Results: The data obtained was tested for its hypothesis with the Repeated Anova test (95% CI). The results showed that the mean serum and plasma glucose levels that were directly examined were 94.8 ± 7.3 mg/dl and 97.48 ± 7.8 mg/dL, which were delayed 1 hour 87.7 ± 7.6 and 92.81 ± 7.79 mg/dL and delayed 2 hours by 81.7 ± 8.03 and 89.3 ± 7.7 mg/dL. Statistical test results showed a significant value (p: 0.000) for differences in blood glucose levels between serum and plasma EDTA which were immediately separated and delayed 1 and 2 hours and p value: 0.059 for differences in serum and plasma glucose levels. Conclusion: It can be interpreted that serum and plasma EDTA glucose levels are not different, but the length of time the delay in separation of serum or plasma from blood cells affects the decrease in glucose levels.